Psychotherapy in the Kurdistan region of Iraq (KRI): Preferences and expectations of the Kurdish host community, internally displaced- and Syrian refugee community. (March 2022) - Böge, Kerem; Hahn, Eric; Strasser, Judith; Schweininger, Stephanie; Bajbouj, Malek; Karnouk, Carine
Background and Aim: The Kurdish Region of Iraq (KRI) is home to Kurds, internally displaced persons, and Syrian refugees. In the last decades, its inhabitants have witnessed a great deal of political instability, which has led to increased rates of psychological distress. Mental illness contrasts with limited access to and availability of mental health services – and so the treatment gap remains high. This study aims to investigate the perspectives, perceptions, and expectations of Syrian refugees, internally displaced persons and KRI host community members concerning mental health care in the governorate of Duhok. Attitudes and perspectives regarding psychotherapy, such as satisfaction with services, effects of therapy, bias toward therapy, and stigma, are explored. Methods: One hundred one participants were recruited from hospitals, clinical settings, and institutions from the governorate of Duhok in the KRI. Participants received the Patient Satisfaction Questionnaire (PSQ) and were asked to evaluate services through four subscales: patient satisfaction, effects of therapy, bias toward therapy, and stigma. Results: Results revealed overall high satisfaction with services and effects of therapy. In contrast, both bias and stigma subscales were rated more ambivalently. Conclusion: Patient satisfaction is key for assessing health care quality, understanding attitudes toward therapy, and help-seeking behavior. Results offer insight for stakeholders in the psychosocial field allowing for a better understanding and improvement of availability and access to quality-driven mental health care services